EVALUATION, ANALYSIS AND REPORTING AT THE BEGINNING OF THE 21ST CENTURY - Kund Miklós Regényi (ANGLISTICUM. Journal of the Association-Institute for English Language and American Studies, 2024)
The fundamental responsibilities of intelligence services, such as assessment, analysis, and reporting, have always been critical, and their importance is only increasing in the first half of the 21st century. The conflict in Ukraine underscores the necessity of precise and dependable analysis and reporting. However, this field has been significantly affected by changes and challenges arising from intelligence-sharing policies and the rapid progress of artificial intelligence. This study delves into how these factors can shape the work of intelligence and reporting in the modern intelligence community.